PENGELOLAAN KARYAWAN EKSPATRIAT: ANALISIS KEBERHASILAN ADAPTASI DAN RETENSI DI NEGARA ASING - Paramayudha, Yudistira; Arwanti, Winda; Perkasa, Didin Hikmah (Jurnal Bina Bangsa Ekonomika, 2025)
This study examines the adaptation and retention of expatriate employees in the context of international human resource management. Adopting a systematic literature review (SLR) approach, the research identifies critical factors influencing expatriate success, including cultural differences, cross-cultural training, organizational support, individual motivation, and family welfare. The findings reveal that integrated strategies, such as pre-departure training, ongoing mentorship during assignments, and policies addressing expatriates' personal and family needs, significantly enhance international assignment outcomes. This research provides strategic insights for multinational corporations to develop innovative HR management policies, fostering a globally competent, adaptable, and competitive workforce in international markets.